PENGARUH PEMBELAJARAN DARING DAN KEDISIPLINAN TERHADAP PRESTASI BELAJAR GEOGRAFI - Meri Andriani; Bayu Insanistyo (DIADIK, 2022)
The purpose of this study was to describe the effect of online learning and discipline on student achievement in Geography and to describe the effectiveness of online learning and discipline to improve student achievement. This research uses experimental research. Data collection was carried out by observation and test, the subject of experimental research was the students of class XI IPS 1, the determination of the experimental class and the control class by means of purposive random sampling. Class X1 IPS 2 as the experimental class and X1 IPS 3 class as the control class. The data were collected by means of a learning achievement test in the form of multiple choice and a questionnaire for discipline. The data were processed statistically using two-way analysis of variance (ANOVA) techniques with a significant stage of 0.05. The results of this study indicate that (1) the learning achievement of students who use Zoom Meeting is higher than students who use google classroom. (2) The learning achievement of students who have high discipline is higher than students who have low discipline. (3) There is an interaction between online learning models and the level of discipline on student achievement